Maternal High Fat Diet Alters Skeletal Muscle Mitochondrial Catalytic Activity in Adult Male Rat Offspring - Pileggi, Chantal A.; Hedges, Christopher P.; Segovia, Stephanie A.; Markworth, James F.; Durainayagam, Brenan R.; Gray, Clint; Zhang, Xiaoyuan D.; Barnett, Matthew P. G.; Vickers, Mark H.; Hickey, Anthony J. R.; Reynolds, Clare M.; Cameron-Smith, David (Frontiers in Physiology, 2016)
A maternal high-fat (HF) diet during pregnancy can lead to metabolic compromise, such as insulin resistance in adult offspring. Skeletal muscle mitochondrial dysfunction is one mechanism contributing to metabolic impairments in insulin resistant states. Therefore, the present study aimed to investigate whether mitochondrial dysfunction is evident in metabolically compromised offspring born to HF-fed dams. Sprague-Dawley dams were randomly assigned to receive a purified control diet (CD; 10% kcal from fat) or a high fat diet (HFD; 45% kcal from fat) for 10 days prior to mating, throughout pregnancy and during lactation. From weaning, all male offspring received a standard chow diet and soleus muscle was collected at day 150. Expression of the mitochondrial transcription factors nuclear respiratory factor-1 (NRF1) and mitochondrial transcription factor A (mtTFA) were downregulated in HF offspring. Furthermore, genes encoding the mitochondrial electron transport system (ETS) respiratory complex subunits were suppressed in HF offspring. Moreover, protein expression of the complex I subunit, NDUFB8, was downregulated in HF offspring (36%), which was paralleled by decreased maximal catalytic linked activity of complex I and III (40%). Together, these results indicate that exposure to a maternal HF diet during development may elicit lifelong mitochondrial alterations in offspring skeletal muscle.